Fighting mobile crime - Rosario Crinò; Giovanni Immordino; Salvatore Piccolo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2018)
We develop a model in which two countries choose their enforcement levels non-cooperatively, in order to deter native and foreign individuals from committing crime in their territory. We assume that crime is mobile, both ex ante (migration) and ex post (fleeing), and that criminals who hide abroad after having committed a crime in a country must be extradited back. We show that, when extradition is not too costly, countries overinvest in enforcement compared to the cooperative outcome:insourcing foreign criminals is more costly than paying the extradition cost. By contrast, when extradition is sufficiently costly, a large enforcement may induce criminals to flee the country in which they have perpetrated a crime. Surprisingly,the fear of extraditing criminals enables countries to coordinate on the efficient (cooperative) outcome.
Keywords: K14; K42; 330; Crime; Enforcement; Extradition; Fleeing; Migration